1997
DOI: 10.1007/bf03014317
|View full text |Cite
|
Sign up to set email alerts
|

Quality and retrieval of obstetrical anaesthesia randomized controlled trials

Abstract: Care must be taken when reviewing obstetrical anaesthesia research. Strategies in addition to a MEDLINE search must be used to identify RCTs since more than one third were missed using MEDLINE alone. Poor quality RCTs are more likely to be biased in favour of a new treatment. Therefore, to increase the validity of reviews sensitivity analyses based on quality should be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In Table 1 we present the available data from the studies that compared the methodological quality of RCTs in various research fields [3e37; Table is available on the journal's website at www.jclinepi.com]. The included studies reported on the methodological changes that were performed during the years in the RCTs of various biomedical fields, including rheumatology [10, 14,15,33,36], gastroenterologyehepatology [12, 23,24], orthopedics [6,9,17], anesthesiology [19,20,27], surgery [13,32], public health/ health services [29,30], intensive care [16,18] [26], psychiatry [25], radiology [35], complementary medicine [22], and general practice [31]. One study [34] examined meta-analyses conducted on the fields of gastroenterology, cardiology, obstetrics, and smoking cessation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In Table 1 we present the available data from the studies that compared the methodological quality of RCTs in various research fields [3e37; Table is available on the journal's website at www.jclinepi.com]. The included studies reported on the methodological changes that were performed during the years in the RCTs of various biomedical fields, including rheumatology [10, 14,15,33,36], gastroenterologyehepatology [12, 23,24], orthopedics [6,9,17], anesthesiology [19,20,27], surgery [13,32], public health/ health services [29,30], intensive care [16,18] [26], psychiatry [25], radiology [35], complementary medicine [22], and general practice [31]. One study [34] examined meta-analyses conducted on the fields of gastroenterology, cardiology, obstetrics, and smoking cessation.…”
Section: Resultsmentioning
confidence: 98%
“…The items included in these scales and the relative importance assigned to each of them varied considerably. In seven studies [9, 14,18,22,23,25,27] 13,15,16,18,22,32,33]), and intention-to-treat analysis (assessed in 11 studies [3,4,6e10,14,15,18,24]). Trial design, statistical analysis, report of adverse events, baseline comparability between groups, outcome specification, eligibility criteria were evaluated in a fewer number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PubMed search, there was no MeSH term corresponding to articles assessing the quality of RCTs; thus all articles published in English between January 1, 1987 and March 7, 2007 were searched using 55 terms around the idea of quality in the title. No limits were used because some articles in PubMed may be misclassified [6,7]. For the Cochrane search, we searched the Cochrane Methodology Register, part of the Cochrane Library, (issue 1, 2007) using the following indexing terms: ''relationship to trial quality,'' ''scales and checklists,'' ''checklists and guidelines,'' ''critical appraisal,'' ''bias in trials.''…”
Section: Electronic Searchmentioning
confidence: 99%
“…Different units in a myriad of studies use all sorts of different analgesic regimens; policies for infusing oxytocics vary; obstetrician and midwife bias is inevitable [87]. Perhaps for these reasons, and because there are many trials of poor quality [88], studies asking apparently the same question find different or conflicting answers. McGrady concluded that the effect of 'extradurals on outcome of labour is overshadowed by that of obstetric practice', a statement that can be generalised to much of anaesthesia.…”
Section: Confounding Factorsmentioning
confidence: 99%